2012
DOI: 10.3892/mmr.2012.837
|View full text |Cite
|
Sign up to set email alerts
|

Cyanate attenuates insulin secretion in cultured pancreatic β cells

Abstract: Abstract. The vast majority of long-term complications in transplanted patients are associated with cardiovascular disease. Previously, an alternative and dominant mechanism for cyanate formation in atherosclerotic lesions has been discovered. This study was designed to determine the effect of cyanate on insulin secretion in cultured pancreatic β cells (INS-1 cells). The cytotoxicity of cyanate was determined by 3-(4,5-Desethyithiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Insulin secretion was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Carbamylation is a posttranslational modification of proteins induced by cyanate in human blood plasma (1). The active form of cyanate, isocyanic acid, reacts irreversibly with the amino-or thiol groups of amino acids in proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbamylation is a posttranslational modification of proteins induced by cyanate in human blood plasma (1). The active form of cyanate, isocyanic acid, reacts irreversibly with the amino-or thiol groups of amino acids in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Carbamylation of low-density lipoprotein (LDL) has thus far been investigated predominantly in the context of uremia (7,8) as urea spontaneously converts to cyanate and ammonia in aqueous solutions (1). However, a recent study demonstrated that thiocyanate, elevated by smoking and diet, is changed into cyanate in human blood plasma (9).…”
Section: Introductionmentioning
confidence: 99%